Medical Makeup for Concealing Facial Scars - Mee, Donna; Wong, Brian J. F. (Facial Plastic Surgery, 2012)
Surgical, laser, and pharmacological therapies are all used to correct scars and surgical incisions, though have limits with respect to how well facial skin can be restored or enhanced. The use of cosmetics has long been a relevant adjunct to all scar treatment modalities. In recent years, technical advancements in the chemistry and composition of cosmetic products have provided the patient with a broader range of products to employ for concealing scars. This review will provide an overview of contemporary methods for concealing facial scars, birthmarks, and pigmentary changes without the use of traditional/dated, heavy appearing camouflage products. Additionally, general guidelines and information will be provided with respect to identifying competent makeup artists for care of the medical patient. The article by no means is meant to be a tutorial, but rather serves as a starting point in this allied field of medicine.
Keywords: scar camouflage; facial plastic surgery; cosmetics; makeup